UROSEPSIS IN THE PRACTICE OF AN OBSTETRICIAN-GYNECOLOGIST (CLINICAL CASE) - Moses, Vadim Gelievich; Ivannikova, Alena Vasilievna; Grishkevich, Elena Valentinovna; Orlova Елена Николаевна; Rudaeva, Elena Vladimirovna; Elgina, Svetlana Ivanovna; Мозес Kira Borisovna (Mother and Baby in Kuzbass, 2026)
Urinary tract infections (UTIs) are a significant cause of perinatal and maternal morbidity and mortality. Although some risk factors for urinary tract infections in pregnant women are well established, factors associated with an increased risk of urosepsis remain less well defined. Pregnant women with anemia, hydronephrosis due to gestational or renoureteral lithiasis, and fever above 38°C (100.4°F) are at increased risk for urosepsis. Although the prognosis for pregnant women with urosepsis is generally favorable, urologic intervention may not prevent a higher incidence of fetal distress and the need for referral to other healthcare facilities compared to pregnant women with uncomplicated upper urinary tract infections.